Using Clustered Regularly Interspaced Short Palindromic Repeats gene editing to induce permanent expression of fetal hemoglobin in β-thalassemia and sickle cell disease: A comparative meta-analysis - Quagliano, Anthony; Acevedo, Daniel; Hardigan, Patrik; Prasad, Samiksha (Frontiers in Medicine, 2022)
β-hemoglobinopathies like sickle cell disease (SCD) and β-thalassemia are characterized by differing mutations in the hemoglobin subunit beta gene (HBB). These disorders vary in phenotypic presentation and severity, with more severe manifestations leading to transfusion dependence along with associated complications such as infection and iron overload. β-hemoglobinopathies symptoms rapidly worsen after birth as the levels of fetal hemoglobin (HbF) begin to decline. To reverse this decline, current treatment plans typically involve the use of pharmacological agents such as hydroxyurea to raise expression levels of HbF. However, these treatments only result in transient effects and must be consistently administered. Gene editing technologies such as CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats- CRISPR associated protein) offer the opportunity to create novel treatments which can raise HbF expression with potential permanent effects. Two gene targets, B-cell lymphoma/leukemia 11A gene (BCL11A) and the promoter regions of gamma globin genes (HBG1/2), have been identified to significantly increase HbF protein expression. In order to differentiate the effectiveness of BCL11A and HBG1/2 editing, a meta-analysis was performed by first identifying 119 studies for inclusion based on the search terms terms “β-Thalassemia”, “beta-thal” “sickle cell disease”, “SCD”, and “CRISPR”. Following application of exclusion and inclusion criteria, we performed analysis on 8 peer-reviewed published studies from 2018-2021 were included in the study. Forest plots were generated using R (version 4.1.2). Primary comparative analysis shows HBG1/2 had a significantly (p<0.01) greater impact on induction of HbF expression compared to BCL11A. This analysis leads us to conclude that HBG1/2 merits further investigation as a possible gene editing target for treatment of (SCD) and β-thalassemia.